Strategi Pembelajaran Berbasis STEM Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika SD/MI - Gusmana, Iin; Syamzaimar, Syamzaimar (Juring (Journal for Research in Mathematics Learning), 2025)
Mathematical problem solving skills are essential competencies in primary education, yet many elementary school students still struggle to understand concepts and apply them effectively. The STEM (Science, Technology, Engineering, and Mathematics) approach offers an alternative learning strategy that is more applicable and contextual to address these challenges. This study aims to analyze the effectiveness of STEM based learning in improving students’ mathematical problem-solving abilities. The research employed a mixed methods approach with an explanatory sequential design, beginning with the collection of quantitative data through problem solving tests, followed by qualitative data from classroom observations and interviews with teachers and students. The research subjects were fifthgrade students at MIN 3 Rokan Hulu. The results indicate that students who participated in STEM-based learning experienced a significant improvement in their problem-solving skills compared to the control group. STEM learning also fostered active engagement, critical thinking, and deeper understanding of mathematical concepts. Nevertheless, the implementation of STEM-based learning faced challenges such as limited facilities, insufficient teacher training, and technical constraints in the field. Therefore, ongoing support in resource development and teacher capacity building is crucial for the optimal implementation of STEM strategies in primary school settings.